Comparative Invention Performance of Major Industrial Countries: Patterns and Explanations - Glismann, Hans H.; Horn, Ernst-Jürgen (Management Science, 1988)
The paper presents an analysis of invention performance, as measured by patenting activities, of six countries (France, Italy, Japan, United Kingdom, USSR, West Germany) relative to the United States for 41 SIC industries over the past 20 years. It turns out that non-U.S. countries as a group have increased their (relative) invention performance in all fields of technology, including high technology fields. In a second step hypotheses which can be supposed to explain the relative decline of the United States' patenting activities are discussed and tested. There is strong evidence that catching up processes contributed most to the relative decrease of the United States; there is only little evidence that government interventions regarding research and development activities have had counterproductive effects on invention performance.